Designing a Virtual Data Warehouse in Supporting Sales Information Needs (Case Study: National Scale Building Material Store X) - Andrew Sumichan; I Made Gede Yudiana; Muhammad Ridwan Satrio; I Made Sudarma (International Journal of Engineering and Emerging Technology, 2019)
National-scale building material stores that have branches in various regions certainly want the business to run smoothly. This must be supported by good sales activities at the central store and also branch stores spread in various places. However, there is no solution to collect sales data from branch shops quickly, causing a slow response to the analysis of the increasing trend in sales of goods and goods whose sales trend has dropped. This can reduce sales competitiveness in this national scale business with similar competitors. Virtual data warehouses can help collect scattered operational data, in this case sales data located at branch stores in various locations are then collected into a data warehouse that is stored in the cloud server so that it can be processed for strategic decisions. Virtual data warehouse is a data warehouse that connects operational databases regardless of where the database is located and regardless of the format, looks as if somewhere and in a consistent format. This study produces a virtual data warehouse structure that applies the kimball nine step design method so that it produces a data warehouse schema model with the star scheme. This study explains the design of a virtual data warehouse that can facilitate analysis of sales data at national scale building material stores that have branches in various places